2000
DOI: 10.4314/sajas.v30i1.3881
|View full text |Cite
|
Sign up to set email alerts
|

Milk production of Tswana goats fed diets containing different levels of energy

Abstract: The aim of this experiment was to characterize the milk yield of the Tswana goat of Botswana. Twenty-one Tswana goat does were allocated to one of three diets formulated to provide energy for maintenance and a milk yield of either 1.5 kg/d, 1.0 kg/d or 0.5 kg/d. Intake, milk yield and kid growth rate was monitored for 14 weeks. Dry matter intakes of up to 5% of body weight were recorded. Energy intake and milk yield differed between treatments (p < 0.01). Daily ME intake for the low, medium and high-energy die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 4 publications
2
5
0
Order By: Relevance
“…Water stress had no significant influence on the rectal temperatures of the ewes as they were maintained within the standard range of 38-39.5°C. Casamassima et al [41] and Adogla-Bessa and Aganga [44] also found the same result in Lacaune ewes and Tswana goats, respectively. El-gawad [50] and Jaber et al [34] reported the same result for Nubian goats and Awassi ewes, respectively, which suffered from salinity stress.…”
Section: Effect Of Water Stress On Physiological Parametersmentioning
confidence: 56%
See 2 more Smart Citations
“…Water stress had no significant influence on the rectal temperatures of the ewes as they were maintained within the standard range of 38-39.5°C. Casamassima et al [41] and Adogla-Bessa and Aganga [44] also found the same result in Lacaune ewes and Tswana goats, respectively. El-gawad [50] and Jaber et al [34] reported the same result for Nubian goats and Awassi ewes, respectively, which suffered from salinity stress.…”
Section: Effect Of Water Stress On Physiological Parametersmentioning
confidence: 56%
“…The high salinity of drinking water seems to negatively influence heart rate by decreasing it, which does not seem to be the case in Ouled Djellal ewes that have experienced a 3day water restriction, as it is maintained within the standards advanced by Meyer [51] for sheep (70-80 bt/min). This result is in contrast to the Tswana goats, which were deprived of water for 72 hours and had a reduced heart rate [44].…”
Section: Effect Of Water Stress On Physiological Parametersmentioning
confidence: 57%
See 1 more Smart Citation
“…Furthermore, when milk is the sole source of food to the preweaned kids, the general condition and the average daily gain of kids are a direct reflection of the amount and the quality of milk produced by the dam (Cimen andKaraalp, 2009 andMartínez-Gonzáleza et al, 2015). The amount of milk produced has a strong influence on kid growth, as 20-80% of the variation in WW was due to the volume of milk produced or suckled (Sibanda, 1992 andAdogla-Bessa andAganga, 2000). Due to the fact that, a close correlation was existed between the OS and mastitis in dairy animal a superiority of oxidizing processes can indicate a subclinical inflammation of the mammary gland.…”
Section: Discussionmentioning
confidence: 99%
“…Preserving green forages on the form of silage for minimal loss of nutritive value due to anaerobic fermentation of soluble carbohydrates to organic acids. (Adogla and Aganga , 2000) found that supplying the right amount of corn silage had the higher improved production of herds. Corn silage can be an economic source of nutrients for dairy animals, particularly on large farms where feeding can be mechanized ( Olker et al, 2009) and ( Wrobel, 2009) explained that microorganisms gas play important roll in silage to improve fermentation which evident by a rapid decline in pH.…”
Section: Introductionmentioning
confidence: 98%